Stadium city: a study of the regional, economic, and transportation components of a transit-oriented development at the Truman Sports Complex - Credit, Kevin (Kansas State University, 2012)
Transit-Oriented Developments (TODs) are an unprecedented typology in the Kansas City region, which predominately exhibits automobile-oriented development characteristics. The Truman Sports Complex in Kansas City, Missouri, home of two professional sports venues, has a unique location on a proposed transit corridor, the Rock Island, planned to run between downtown Kansas City and suburban Lee's Summit. Therefore, the site is a natural choice for a TOD. Building a TOD at the Truman Sports Complex will create a focal point on the Rock Island Corridor that connects Arrowhead and Kauffman Stadiums to downtown Kansas City and Lee's Summit via a regional transit system; bring together a diverse population through the creation of a walkable, mixed-use center located adjacent to the regionally known cultural institutions; and encourage new development around the junction of Interstates 70 and 435, a major transportation node in Kansas City, Missouri. This study employs extensive regional, market, and transportation analyses to inform specific planning and programming ideas. It draws from a large body of literature and precedents, incorporating well established elements and principles into a new development that is unique among TODs and sports-related districts. The project’s findings reveal that retail, multi-family housing, and office development at the Truman Sports Complex, supported by rail transit and strong tenants, would fill a void in regional business and population density close to downtown, and have the potential to be economically viable as a regional center through 2040. This research has also shown that in order to achieve the adequate density for pedestrian vitality on the site, high-rise development with limited single-family options is necessary. And perhaps the most important finding is that the rail line should be rerouted through the center of the site if Transit-Oriented Development at the Truman Sports Complex is pursued, in order to maximize the pedestrian-accessibility of land suitable to development and ensure that activity is concentrated around the stadiums. Overall, the significance of this project is that it can inform the Mid-America Regional Council, the Jackson County Sports Complex Authority, and other relevant stakeholders about the potential for developing on this site, and it demonstrates that a mixed-use, pedestrian-friendly, large-scale transit-oriented development with a wide variety of program is both viable and desirable at the Truman Sports Complex.
Keywords: Transit-oriented development; Sports stadium; Market analysis; Urban design; Kansas City; Transportation (0709); Urban Planning (0999)